Process development of the device using in-house plate-to-plate tool with nanoimprint lithography technique for biochip application - Samsuri, Fahmi B. (2013)
Biochip is a promising device with capabilities of performing sorting, trapping and screening a large number of biological samples in a short time. Fabrication of biochip pattern process leads to an opening study towards the development of a working biochip. The traditional photolithography process have a limitation in achieving high throughput for biochip pattem fabrication. In this research, the fab1ication process of biochip pattern was developed and the imprint parameter for biochip pattern using an in-house assembled plate-to-plate tool was investigated. The biochip pattems are prepared from existing projection lithography to create the mold. Using soft lithography technique, the biochip pattem was replicated invertly in the PDMS mold.